2015
DOI: 10.1186/s12954-015-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional assessments of participants’ characteristics and loss to follow-up in the first Opioid Substitution Therapy Pilot Program in Kabul, Afghanistan

Abstract: BackgroundKabul has over 12,000 people who inject drugs (PWID), most of them heroin users, and opioid substitution therapy has recently been introduced as an effective method to reduce opioid use. We aimed to evaluate a pilot Opioid Substitution Therapy Pilot Program (OSTPP) in Kabul, Afghanistan, particularly to (1) describe characteristics of the participants enrolled in the program and (2) identify factors associated with client retention in the OSTPP.FindingsTwo cross-sectional surveys evaluated participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 19 publications
0
25
1
Order By: Relevance
“…One explanation for failure to find many associations is that the dropout rates were low, limiting our ability to find associations. Multiple studies have found age and employment to be significant predictors of retention, [16][17][18][19][20][21][22][23][24][25][26][27] whereas we find evidence only that patients reporting that they were homemakers, retired, or students are more likely to dropout than patients who have jobs. We also found in interviews with patients who dropped out that conflicts with job schedules were an important cause of drop out, which contrasts with the quantitative association between homemakers, retired persons, or students and dropout.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…One explanation for failure to find many associations is that the dropout rates were low, limiting our ability to find associations. Multiple studies have found age and employment to be significant predictors of retention, [16][17][18][19][20][21][22][23][24][25][26][27] whereas we find evidence only that patients reporting that they were homemakers, retired, or students are more likely to dropout than patients who have jobs. We also found in interviews with patients who dropped out that conflicts with job schedules were an important cause of drop out, which contrasts with the quantitative association between homemakers, retired persons, or students and dropout.…”
Section: Discussioncontrasting
confidence: 75%
“…We found that marital status and HIV status are associated with dropout, in keeping with previous literature. 16,17,24,26,[29][30][31] This information could help to target interventions to improve retention.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were published from 2000 to 13th August 2021. Fourteen studies were conducted in Afghanistan [29,31,41,[43][44][45][46][53][54][55][56][57][58][59], one study was with Afghan refugees in Pakistan [62], nine were in Colombia [32-38, 60, 61], ten were in Myanmar [30,39,40,42,[47][48][49][50][51][52] and one was in China and Myanmar [63]. Thirty were cross-sectional in design, four were cohort studies and one case-control study.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…A study in Medellin, a city in Colombia, reported that 63.4% of the sample sold drugs [35]. Between 50 and 60% of Afghanistan populations reported a history of imprisonment [41,45,57] between 4 and 20% were homeless or unstably housed across the three countries [38,42,59,62] and between 15 and 52.4% were unable to read or write in Myanmar and Afghanistan [44,46,51]. In all studies except one, the majority of the sample were male (82-100%).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation